Why Sexual Violence is a Weapon of War in Jacqui True’s Perspective : Learning from sexual Violence in Congo’s Conflict 2021-2024 - Amalia, Ridha; Ghaniya, Avinda (Review of International Relations, 2024)
The use of sexual violence as a weapon of war in the Democratic Republic of Congo (DRC) has become one of the most widespread and destructive forms of gender-based violence. This article explores why sexual violence is used so extensively in the DRC. Using Jacqui True’s feminist perspective within a structural violence framework, it examines three main factors: gender norms and patriarchal structures, weak legal frameworks, and socio-economic disparities. A case study of the DRC shows how these factors work together to make sexual violence a strategic tool in war. The authors argue that sexual violence in war is not merely a consequence of conflict but also a symptom of deeper structural inequalities. The article concludes by emphasizing the importance of addressing these inequalities to reduce the use of sexual violence as a weapon of war and recommends policies focused on gender justice and survivor protection.